Bioassay using the water soluble fraction of a Nigerian light crude oil on clarias gariepinus fingerlings (2012)
A 96-hour bioassay was conducted using the water soluble fraction of a Nigerian light crude oil sample on Clarias gariepinus fingerlings. 0, 2.5, 5.0, 7.5 and 10 mls of water soluble fractions (WSF) of the oil were added to 1000 litres of de-chlorinated tap water to form 0, 25, 50 , 75 and 100 parts per million representing treatments 1 to 5 respectively. Each treatment had two replicates with fifteen fish per replicate. At the end of the 96-hour period of exposure, the fish were transferred into separate bowls containing fresh water without oil for recovery for ten more days. Heavy metal and total hydrocarbon contents of the water and fish were analyzed at 96 hour and 14 days which marked the end of the recovery period. No mortalities were recorded on all treatments during the 96-hour period. Mortalities were observed between 120 and 144 hours after the onset of the experiment with the maximum number of dead fish (p<0.05) from treatment 5(100 ppm WSF) during the recovery period indicating a delayed response to the WSF by the fish. No mortalities were recorded after 144 hours till the termination of the experiment at 14 days . The 96-hour LC50 could not be calculated since no deaths occured during the period. The Total hydrocarbon contents of the water were 0, 0.026 ,0.316 ,0.297, 0.253 mg/l for treatments 1(0 ppmWSF)) to 5(100ppmWSF) respectively. Lead , iron and cadmium were not detected in water during the study, lead was also not detected in fish muscles from all treatments. The iron contents of all the treatments were lower than the control except for treatment 3(50 ppm WSF). THC concentrations in fish were higher at 96 hours and 14days than in the water indicating bioconcentration in fish and a retention in the fish long after exposure.